2022
DOI: 10.1111/codi.16247
|View full text |Cite
|
Sign up to set email alerts
|

A new overlapped delta‐shaped anastomosis technique using linear staplers with reinforced bioabsorbable material for intracorporeal anastomosis during laparoscopic colectomy

Abstract: Aim Totally laparoscopic colectomy with intracorporeal anastomosis (IA) is associated with less surgical trauma and wound related complications compared to laparoscopy‐assisted colectomy with extracorporeal anastomosis. Delta shaped anastomosis is a widely popular IA technique. In this study, we discuss a construction technique for an overlapped delta‐shaped anastomosis using a linear stapler with a reinforced bioabsorbable material. Methods We excised the bowel at a point 10 cm from the tumour on either sides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The median anastomosis construction time was 12 min, which was shorter than the 17 min for the robotic IA procedure and the 13 min for the laparoscopic IA procedure [13]. When performing common enterotomy closure, slow‐speed firing of the linear stapler is necessary because the staple lines cross each other [12]. Consequently, we exercised caution when using the linear stapler for common enterotomy closure by pressing the rotator button twice to activate the slow‐speed firing mode in the Signia Stapling Technology [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The median anastomosis construction time was 12 min, which was shorter than the 17 min for the robotic IA procedure and the 13 min for the laparoscopic IA procedure [13]. When performing common enterotomy closure, slow‐speed firing of the linear stapler is necessary because the staple lines cross each other [12]. Consequently, we exercised caution when using the linear stapler for common enterotomy closure by pressing the rotator button twice to activate the slow‐speed firing mode in the Signia Stapling Technology [12].…”
Section: Discussionmentioning
confidence: 99%
“…When performing common enterotomy closure, slow‐speed firing of the linear stapler is necessary because the staple lines cross each other [12]. Consequently, we exercised caution when using the linear stapler for common enterotomy closure by pressing the rotator button twice to activate the slow‐speed firing mode in the Signia Stapling Technology [12]. Closing a common enterotomy with a single or double handsewn suture during side‐to‐side overlapped anastomosis is a widely adopted method and is considered both straightforward and safe for RRC with IA [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, colorectal cancer (CRC) is now the third most common cancer and a signi cant cause of cancer-related deaths worldwide Colorectal adenomas are a signi cant cause of colorectal cancer [1] .In the early stage of CRC, due to the absence of typical symptoms, it is not easy to detect, and has high morbidity and mortality [2] .Complete laparoscopic radical resection of colorectal cancer has become one of the important links of digestive tract reconstruction in colorectal cancer due to its safety and feasibility, low surgical trauma, quick postoperative recovery, short hospital stay and other advantages [3] .At present, the conventional anastomosis method is di cult to operate, which shows the reverse peristaltic anastomosis [4] ,often results in the failure of the operation. In order to make use of the operation simplicity of laparoscopic triangular anastomosis and avoid the opposite direction of intestinal peristalsis after digestive tract reconstruction, so as to be more in line with physiological functions, the author's team modi ed this anastomosis mode, namely, proximal and distal intestinal tubes were overlapped before anastomosis, overlapped delta-shaped anastomosis (ODA) [5] .Many studies have shown that overlapping triangulation has high safety and good prognosis [6][7][8][9][10][11] .However, there is a lack of high-level evidence-based medical evidence for objective evaluation of overlapping triangulation. Therefore, the aim of this study was to investigate the safety and e cacy of the overlapping triangular anastomosis by comparing it with other anastomoses by integrating and analyzing previous studies through Meta-analysis, and to provide evidence-based medical evidence for clinical practice.…”
Section: Introductionmentioning
confidence: 99%